Chronic obstructive pulmonary disease and its impact on the patient's quality of life: an integrative review (Research, Society and Development, 2023)
Introduction: Chronic obstructive pulmonary disease (COPD) is responsible for a large part of the mortality due to respiratory diseases worldwide, being caused by an obstruction of the upper and lower airways, and may include diseases such as emphysema and bronchitis. Its emergence is related to the conditions to which the individual is exposed, such as air pollution in large urban centers and work environments with toxic substances. Objective: To analyze how chronic obstructive pulmonary disease (COPD) impacts the quality of life of patients with it. Methodology: This article is classified as an integrative literature review. For the composition of the work, the databases of scientific articles were used, among them: US National Library of Medicine (PubMed) and Scientific Electronic Library Online (SciELO) Latin American and Caribbean Literature in Health Sciences (LILACS) and Biblioteca Virtual em Saúde (BVS) of scientific data until January 10, 2022, in English, Portuguese and Spanish. As inclusion criteria, the articles used are from the period 2080 to 2022. The keywords “COPD" AND “quality of life” were used for the search. Result and discussion The disease has a very fast progressive character, if not treated it has a high aspect of mortality and can lead to other health problems such as cardiac dysfunctions and sleep disorders.Conclusion: There is still a lack of public policies to raise awareness about the importance of care in the face of the diagnosis of COPD, with adherence to treatment being the main focus.